Problems And Efforts To Form Pedagogic Competence For Prospective Islamic Religious Education Educators In The PAI STAI Study Program Sumatra Medan - Mahariah Mahariah (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
Pedagogic competencies are urgently needed by teachers, but unfortunately, learning in tertiary institutions is not fully capable of forming these competencies. There are several problems that are often experienced, but several universities certainly have their own efforts to overcome them. This study aims to analyze the problems of pedagogic competence of prospective PAI educators, efforts to establish pedagogic competence of prospective PAI educators, and success factors in efforts to establish pedagogic competence of prospective PAI educators. The research was carried out at the PAI STAI Sumatra Medan study program using a qualitative research type based on a case study approach. Research informants, namely study program leaders, lecturers, and students of the PAI study program, The results of the study reveal that: (1) the problems of pedagogic competence in PAI educator candidates, namely the distribution of subjects that are not dominant in pedagogic competence, learning is not yet fully practical or field study in nature, prospective educators master the material but it is difficult to manage learning, prospective educators often apply style classical teaching, domination of mastery of western-based pedagogical competencies; (2) efforts to establish the pedagogic competence of prospective PAI educators are carried out in four steps, namely updating the curriculum, establishing a laboratory tsanawiyah madrasah, skill-based learning orientation, forming an integration-based academic culture; (3) the success factor in the effort to establish competence can be seen from the positive student response to the various steps implemented by the study program leaders, especially the establishment of a laboratory tsanawiyah madrasah.